Association of daily physical activity level with health-related factors by gender and age-specific differences among Korean adults based on the sixth (2014-2015) Korea national health and nutrition examination survey - Chung, Nana (J Exerc Nutrition Biochem, 2017)
[PURPOSE]: This study examined the effects of daily physical activity level on health-related factors according to gender and identified age-specific differences among Korean adults. [METHODS]: Using data from the Korea National Health and Nutrition Examination Survey VI (2014-2015), we selected adults aged 19-64 years who participated in both a health examination and health interview survey. The study included 6,457 participants 19-64 years of age (2,611 men, 3,846 women). [RESULTS]: Assessment of the differences in health-related factors according to age and physical activity in men and women by repeated two-way analysis of variance (ANOVA) revealed significant interaction effects on total cholesterol (TC) and triglyceride (TG) levels and diastolic blood pressure (DBP) in male participants, but there were no significant interaction effects for any health-related factors in female participants. The group of female participants aged 40-64 years with daily physical activity levels over 200 kcal showed a significantly increased prevalence of 46% for dyslipidemia compared to that in female participants with daily physical activity levels below 200 kcal. Physical activity was positively correlated with weight and high-density lipoprotein cholesterol (HDL-C) levels in men 19-39 years of age, compared to weight, waist circumference (WC), body mass index (BMI), and DBP in men 40-64 years of age, and weight, WC, BMI, glycated hemoglobin (HbA1c) and triglyceride (TG) levels in women 19-39 years of age. In women 40- 64 years of age, physical activity was especially significantly positively correlated with weight, BMI, HDL-C and negatively correlated with fasting glucose and TG levels. [CONCLUSION]: In male and female participants, the 40-64-year age group showed negative results for health-related factors compared to those in the 19-39-year age group. The higher the weight, WC, BMI, the higher is the physical activity level. Physical activity levels were significantly positively correlated with health-related variables.